Human resource management practices and organizational injury rates. (September 2021) - Turner, Nick; Barling, Julian; Dawson, Jeremy F.; Deng, Connie; Parker, Sharon K.; Patterson, Malcolm G.; Stride, Chris B.
Highlights: Do organizational-level human resource management (HRM) practices predict organizational-level injury rates? HRM practices were systematic selection, extensive training, performance appraisal, high relative compensation, and empowerment. HRM practices were assessed by independent observers and organizational injury rates were collected from a national regulator. Results from 49 UK organizations indicated that only empowerment predicted lower organizational-level injury rates. Abstract: Introduction: This study investigated the extent to which five human resource management (HRM) practices—systematic selection, extensive training, performance appraisal, high relative compensation, and empowerment—simultaneously predicted later organizational-level injury rates. Methods: Specifically, the association between these HRM practices (assessed via on-site audits by independent observers) with organizational injury rates collected by a national regulatory agency one and two years later were modeled. Results: Results from 49 single-site UK organizations indicated that, after controlling for industry-level risk, organization size, and the other four HRM practices, only empowerment predicted lower subsequent organizational-level injury rates. Practical Applications: Findings from the current study have important implications for the design of HRM systems and for organizational-level policies and practices associated with better employee safety.